Collusion-resistant cross-chain transaction scheme based on game theory and verifiable consensus - JIA Xuedan; WANG Liangmin; HUANG Longxia (Tongxin xuebao)
Existing cross-chain transaction solutions often overlook the issue of cross-chain collusion. In response, the counter-collusion cross-channel was proposed to facilitate scalable and collusion-resistant cross-chain transactions. Firstly, a strategy for establishing multiple-relay channels was introduced, including relay chain observers. These channels serve as off-chain pathways connecting users from different business chains, thereby facilitating private and scalable cross-chain transactions. Secondly, a collusion-resistant cross-chain transaction protocol based on game-theoretic incentives was designed, stimulating distrust among colluders to deter cross-chain collusion and uphold transaction security. Thirdly, a layered verifiable cross-chain consensus method was proposed, relying on channel state proofs to ensure secure cross-chain settlement. Formal analyses of participant game dynamics demonstrate that non-collusion emerges as the dominant strategy for channel users under reasonable assumptions. Experimental results indicate that the proposed scheme effectively prevents cross-chain collusion while achieving high cross-chain throughput and scalability compared to traditional relay-based cross-chain solutions.